Optimization and Characterization of Exo-β-Glucanase Produced by Aspergillus flavus on Rice Bran and Oil Palm Fibre: Exo-β-Glucanase produced by Aspergillus flavus on Rice Bran and Oil Palm Fibre - Doughari, James Hamuel; Onuoha, Chikezie Chukwunonye (International Journal of Applied Biology, 2024)
Glucanases are important industrial enzymes that catalyze the hydrolysis of glucan into oligosaccharides. Commercial β-glucanases are produced from microorganisms such as Penicillium chrysogenum, Aspergillus flavus, Pseudomonas fluorescens etc. The increasing application of glucanases in various industries has called for continuous search for a cheaper means of glucanase production. In this study, β-Glucanases were produced from Aspergillus flavus isolated from rice and oil mill refuse dump sites using rice bran and oil palm fibre as substrates. Production was carried out in a submerge fermentation. Optimum activities of crude Aspergillus flavus exo-β-glucanases were 2.36 and 2.34 µmol/ml/min at incubation period of 96 hours (rice bran) and 120 hours (oil palm fibre) respectively; 2.42 and 2.54 µmol/ml/min at pH 6.5 (rice bran) and 5.0 (oil palm fibre) respectively; 2.61 and 2.55 µmol/ml/min at temperature of 35 °C (rice bran) and 40 °C (oil palm fibre) respectively. Yeast extract gave the highest enzyme activity of 2.31 µmol/ml/min. The enzymes were precipitated with 80% ammonium sulphate resulting in 1.18 (rice bran) and 1.15 (oil palm fibre) purification fold. With dialysis tubing, results showed 1.50 (rice bran), 2.50 (oil palm fibre) purification fold. The addition of chloride salts and inhibitors influenced the enzyme activities by either increasing or decreasing the activity values. Results obtained from this work indicate that rice bran and oil palm fibre can be used effectively in the production of exo-β-glucanase under submerged fermentation system using Aspergillus flavus.